Perbandingan Hasil Analisis Biokimia Urin pada Kucing Penderita Obstruksi Uretra: Evaluasi Metode Kateterisasi dan Cystosintesis - Zamzami, Rumi Sahara; Yulian Syah, Nanda; Ferdian, Riyan; Hasan, Muhammad; Sari, Wahyu Eka; Daniel, Daniel; Riandi, Lian Varis (Jurnal Veteriner; Vol 26 No 2 (2025)DO - 10.19087//jveteriner.2025.26.2.238, 2025)
Urethral obstruction is a critical urological condition in cats that necessitatesprompt diagnostic evaluation for appropriate therapeutic management. Urine samplcollection is a pivotal procedure for assessing urinary parameters that aid in diagnosis andclinical decision-making. Two commonly employed methods for urine collection, namelycystosintesis and catheterization, are frequently utilized in clinical practice; however, direccomparisons of urinalysis outcomes between these techniques remain limited. This studyaimed to compare urinalysis results obtained via cystosintesis and catheterization in cats presenting with urethral obstruction. Evaluated parameters included the presence of blood, bilirubin, ketones, glucose, protein, nitrites, white blood cell count (WBC), and urinespecific gravity. A paired-sample design was employed, whereby urine samples weresequentially collected using both methods from the same subjects. Ordinal data (e.g., negative, +, ++, +++) were converted into numerical scores, and statistical analysis waperformed using the non-parametric Wilcoxon Signed-Rank Test. The results demonstrated that most parameters—including the presence of blood, glucose, nitrites, and urine specifigravity—yielded identical values between the two methods. Minor differences wereobserved in the levels of bilirubin, ketones, protein, and WBC in some subjects; however, these differences did not reach statistical significance (p > 0.05). In conclusion, both cystosintesis and catheterization yield comparable urinalysis data in cats with urethra obstruction. Therefore, the choice of urine collection method may be guided by clinical considerations and resource availability without compromising diagnostic accuracy. These findings support the use of either technique as a reliable alternative for evaluating urinary parameters in affected cats.